Scaling Runtimes for Irregular Algorithms to Large-Scale NUMA Systems. - Lenharth, Andrew; Pingali, Keshav (Computer (00189162), 2015)
The Galois system can automatically parallelize irregular algorithms written in a serial programming model and execute them efficiently on nonuniform memory access (NUMA) machines. Experimental results for five complex irregular algorithms show that the system scales up to 420× on large NUMA systems at 512 threads.